Le registre de croisade inédit de saint Louis (1248-1254) - Claverie, Pierre-Vincent, (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2025)
This volume publishes the content of 133 charters of Saint Louis, issued in the East during his first crusade. They come from the Latin manuscript 9778 of the National Library of France, which went overseas with the monarch. These documents from 1248 to 1254 shed light on the operation of the royal household in the Levant. In particular, they highlight two prosperous periods in 1250 and 1252, which saw the king granting a series of privileges from Acre and Caesarea of Palestine, and allow us to follow the early careers of new men coming from the Holy Land and France. Ce volume publie le texte de 133 chartes de saint Louis, émises en Orient durant sa première croisade. Elles émanent du manuscrit latin 9778 de la Bibliothèque nationale de France, qui accompagna le monarque outre-mer. Ces documents des années 1248 à 1254 éclairent le fonctionnement de l'Hôtel du roi au Levant. Deux périodes fastes se détachent avec les années 1250 et 1252, qui virent le roi concéder des vagues de privilèges à partir d'Acre et de Césarée de Palestine. Le registre de croisade présente le mérite de suivre le début de carrière d' homines novi de Terre sainte et de France.